2011
DOI: 10.1200/jco.2010.33.2312
|View full text |Cite|
|
Sign up to set email alerts
|

Dissecting Therapeutic Resistance to RAF Inhibition in Melanoma by Tumor Genomic Profiling

Abstract: A detailed understanding of the mechanisms by which tumors acquire resistance to targeted anticancer agents should speed the development of treatment strategies with lasting clinical efficacy. RAF inhibition in BRAF-mutant melanoma exemplifies the promise and challenge of many targeted drugs; although response rates are high, resistance invariably develops. Here, we articulate overarching principles of resistance to kinase inhibitors, as well as a translational approach to characterize resistance in the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
723
2
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 896 publications
(751 citation statements)
references
References 121 publications
16
723
2
10
Order By: Relevance
“…MEK1/2 mutations, including MEK1 Q56P , have been implicated in both single-agent BRAF and combination BRAF/MEK targeting therapy-acquired resistance in patients (18,21,(34)(35)(36). Single-agent assays demonstrated that relative to the parental BRAF V600E ::MEK1 wt cells, the double-mutant BRAF V600E ::MEK1 Q56P cells displayed a markedly reduced sensitivity to the BRAF inhibitors vemurafenib and dabrafenib and the MEK inhibitor trametinib (Fig.…”
Section: Bvd-523 Exhibits Activity In In Vitro Models Of Braf and Mekmentioning
confidence: 99%
See 1 more Smart Citation
“…MEK1/2 mutations, including MEK1 Q56P , have been implicated in both single-agent BRAF and combination BRAF/MEK targeting therapy-acquired resistance in patients (18,21,(34)(35)(36). Single-agent assays demonstrated that relative to the parental BRAF V600E ::MEK1 wt cells, the double-mutant BRAF V600E ::MEK1 Q56P cells displayed a markedly reduced sensitivity to the BRAF inhibitors vemurafenib and dabrafenib and the MEK inhibitor trametinib (Fig.…”
Section: Bvd-523 Exhibits Activity In In Vitro Models Of Braf and Mekmentioning
confidence: 99%
“…Genetic mechanisms of acquired resistance to single-agent BRAF inhibition have been intensely studied; some examples of identified resistance mechanisms include splice variants of BRAF (16), BRAF V600E amplification (17), MEK mutations (18), NRAS mutations, and RTK activation (19,20). Resistance mechanisms in the setting of BRAF/MEK inhibitor combination therapy are beginning to emerge and mirror that of BRAF single-agent resistance (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…The most common resistant mechanism is MAPK pathway reactivation, which is caused by genetic mutation of MEK or different Ras isoforms (7)(8)(9), upstream activation of receptor tyrosine kinases (RTK) such as FGFR3 and c-Met (10,11), expression of B-RAF V600E splice variants that dimerize in presence of the B-RAF inhibitor (12), amplification of B-RAF (13,14), and upregulation of MAP3Ks such as COT or C-RAF (15,16). Alternatively, activation of MAPKredundant pathways such as PI3K/Akt as a consequence of PTEN loss (17) or overexpression of RTKs such as PDGFRb and IGF1R have also been reported to induce resistance in B-RAF V600E melanoma (7,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical efficacy of these agents is limited by the rapid emergence of drug resistance, which remains a substantial challenge to the clinical management of advanced cancers (21,(25)(26)(27)(28). To our knowledge, this is the first report on the mechanism of acquired resistance to the RET inhibitor describing a link between Src-dependent survival signal activation and drug resistance in RET fusion-positive LADC.…”
Section: Discussionmentioning
confidence: 91%